1995
DOI: 10.1523/jneurosci.15-05-03571.1995
|View full text |Cite
|
Sign up to set email alerts
|

L-glutamate-induced responses and cGMP-activated channels in three subtypes of retinal bipolar cells dissociated from the cat

Abstract: Effects of L-glutamate (Glu), the neurotransmitter released by photoreceptors, on isolated cat bipolar cells were examined. Membrane currents of bipolar cells were recorded by the patch-clamp technique in a conventional whole-cell recording configuration using pipettes containing 1 mM cGMP, which has been known to activate a cationic current sensitive to Glu in ON-type bipolar cells. ON-type bipolar cells (depolarized by light in in situ) and OFF-type bipolar cells (hyperpolarized by light) were identified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 39 publications
7
100
0
Order By: Relevance
“…Error bars represent SEM. Villa et al, 1995;Wang and Robinson, 1997;Walters et al, 1998;Shiells and Falk, 2001), although the G-protein G o , rather than transducin, may be involved in postsynaptic mechanisms of these cells (Nawy, 1999). Induction of cGMP-gated currents by BNP is consistent with the fact that NPs elevate intracellular cGMP levels by activating their pGC-coupled receptors (Blute et al, 2000;Herring et al, 2001).…”
Section: Expression Of Functional Npr In Rat Bipolar Cellsmentioning
confidence: 57%
“…Error bars represent SEM. Villa et al, 1995;Wang and Robinson, 1997;Walters et al, 1998;Shiells and Falk, 2001), although the G-protein G o , rather than transducin, may be involved in postsynaptic mechanisms of these cells (Nawy, 1999). Induction of cGMP-gated currents by BNP is consistent with the fact that NPs elevate intracellular cGMP levels by activating their pGC-coupled receptors (Blute et al, 2000;Herring et al, 2001).…”
Section: Expression Of Functional Npr In Rat Bipolar Cellsmentioning
confidence: 57%
“…Dialysis of salamander ON bipolar cells with cGMP potentiates the standing inward current, but still allows glutamate to suppress this current completely, thus increasing the size of the response to exogenously applied glutamate and to light (Nawy and Jahr, 1990a;Shiells and Falk, 1990;Nawy and Jahr, 1991). Noise analysis of the cation current in dissociated ON bipolar cells from cat retina suggested that dialysis with cGMP dramatically increases the open channel probability (de la Villa et al, 1995). In all of these studies, cGMP was applied under conditions where a fraction of the currently was tonically activated.…”
Section: Elevated Cgmp Levels Improves Signal Detection Near Thresholdmentioning
confidence: 99%
“…Pharmacological interruption of synaptic transmission suggests that these changes most likely occur within the On bipolar cell (Gurevich and Slaughter, 1993), and although the cellular mechanisms involved remain unknown, several research groups have found that mGluR6-mediated responses to glutamate and light are potentiated by intracellular addition of cGMP (Nawy and Jahr, 1990;Falk, 1990, 2002;de la Villa et al, 1995), making it well suited as a modulator of sensitivity.…”
Section: Introductionmentioning
confidence: 99%